Cerebral vs. Cardiovascular Responses to Exercise in Type 2 Diabetic Patients - Kim, Yu-Sok; van der Ster, Björn J. P.; Brassard, Patrice; Secher, Niels H.; van Lieshout, Johannes J. (Frontiers in Physiology, 2021)
The human brain is constantly active and even small limitations to cerebral blood flow (CBF) may be critical for preserving oxygen and substrate supply, e.g. during exercise and hypoxia. Exhaustive exercise evokes a competition for the supply of oxygenated blood between the brain and the working muscles and inability to increase cardiac output sufficiently during exercise may jeopardize cerebral perfusion of relevance for diabetic patients. The challenge in diabetes care is to optimize metabolic control to slow progression of vascular disease, but likely because of a limited ability to increase cardiac output, these patients perceive aerobic exercise to be more strenuous than healthy subjects and that limits the possibility to apply physical activity as a preventive lifestyle intervention. In this review, we consider the effects of functional activation by exercise on the brain and how it contributes to understanding the control of CBF with the limited exercise tolerance experienced by type 2 diabetic patients. Whether a decline in cerebral oxygenation and thereby reduced neural drive to working muscles plays a role for “central” fatigue during exhaustive exercise is addressed in relation to brain’s attenuated vascular response to exercise in type 2 diabetic subjects.